Modeling and daily operation optimization of a distributed energy system considering economic and energy aspects. (7th May 2018) - Tan, Yuhua; Wang, Xin; Zheng, Yihui
Summary: This paper presents a distributed energy system (DES) for a local district and formulates a constrained nonlinear multiobjective optimization model for the daily operation of the system. The main objective of the study is to increase the efficiency by minimizing energy cost, energy consumption, and energy losses. It is implemented through the integration and complementation of renewable energies and fossil fuels as well as the recycling utilization of waste heat in the DES. The consideration of network topology and energy losses of water heating network could also contribute to the improvement of energy efficiency. To solve the optimization problem, a novel Whale Optimization Algorithm is employed. Furthermore, the economic and energy performance of the DES are evaluated and compared with that of conventional centralized energy systems, ie, the EG and MG energy‐supply modes. After simulation studies, the hourly optimal energy (both natural gas and electricity) purchasing schedule as well as the hourly optimal set points of mass water flow rates and supply/return water temperatures could be determined. The results show that the DES saves more than 50% of energy costs/energy consumption than the MG mode and over 22% than the EG mode for a whole day, verifying the competitive advantage and great potential of both energy saving and cost reduction of the DES. Abstract : A distributed energy system considering distributed generation, renewable energy utilization, and waste heat recovery is presented. To increase system efficiency by minimizing energy cost, energy consumption, and energy losses, daily operation problem of the system is formulated as a constrained nonlinear multiobjective optimization model and solved with the novel Whale Optimization Algorithm. The study illustrates that the proposed system could save at least 22%, or up to 50% of energy costs/energy consumption than conventional centralized energy systems.